2011
DOI: 10.1182/blood-2010-05-285742
|View full text |Cite
|
Sign up to set email alerts
|

Tax ubiquitylation and SUMOylation control the dynamic shuttling of Tax and NEMO between Ubc9 nuclear bodies and the centrosome

Abstract: The human T-lymphotropic virus type I oncoprotein Tax is critical for T-cell transformation, acting mainly through nuclear factor kappa B essential modulator (NEMO) binding and subsequent nuclear factor-B activation. Tax localizes to Tax nuclear bodies and to the centrosome and is subjected to ubiquitylation and small ubiquitin-like modifier (SUMO)ylation, which are both necessary for complete transcriptional activation. Using the photoconvertible fluorophore Dendra-2 coupled with live video confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 34 publications
(64 reference statements)
1
72
1
Order By: Relevance
“…Polyubiquitination of Tax plays a critical role in IKK␥ binding, Tax trafficking, and NF-B activation (20,27). However, the regulation of Tax polyubiquitination and NF-B activation by host proteins is poorly understood.…”
Section: Stambpl1 Is a Positive Regulator Of Tax-mediated Nf-b Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyubiquitination of Tax plays a critical role in IKK␥ binding, Tax trafficking, and NF-B activation (20,27). However, the regulation of Tax polyubiquitination and NF-B activation by host proteins is poorly understood.…”
Section: Stambpl1 Is a Positive Regulator Of Tax-mediated Nf-b Signalmentioning
confidence: 99%
“…Tax undergoes a number of posttranslational modifications, including ubiquitination and sumoylation, that regulate Tax trafficking in cells (27). Whereas ubiquitinated Tax is predominantly found in the cytoplasm, sumoylated Tax is located primarily in the nucleus.…”
Section: Stambpl1 Is a Positive Regulator Of Tax-mediated Nf-b Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitination, sumoylation, acetylation, and phosphorylation of Tax have been shown to influence its transcriptional function (5,9,22,23,25,28,34,35,40). Tax ubiquitination has been reported to be required for its activation of NF-B, and it has been found that the Tax-polyubiquitin chains are predominantly K63 linked (40).…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic retention is essential for IKK and NF-kB activation, and may be important for exosome localization as detailed earlier . HTLV-1 Tax also undergoes sumolyation, which aids in nuclear retention and the formation of nuclear bodies that consist of Tax and binding partners CBP and p300 (Kfoury et al, 2011). The sites for sumoylation on the protein overlap with the sites of ubiquitination.…”
Section: Isoforms Of Htlv-1 Tax Are Present In Exosomes Isolated Frommentioning
confidence: 99%